Endogenous hydrogen sulfide homeostasis is responsible for the difference in osmotic stress tolerance in two cultivars of Vigna radiate - Ge, Zhenglin; Cao, Jiaqi; Zhang, Hejia; Hu, Huixin; Geng, Lingxi; Yang, Yufan; Su, Hongfei; Zhang, Xiangyi; Wu, Mingzhu; Yuan, Xingxing; Xie, Yanjie (Environmental and experimental botany, 2022)
Hydrogen sulfide (H2S) has been proved to possess many biological functions and it is an essential component of plant osmotic signaling. However, how endogenous H2S homeostasis is maintained and how this function determines mung bean osmotic tolerance is less explored. To fully answer this question, two cultivars with different osmotic stress tolerance (namely MM015 and MM047) were used in this study. Under osmotic stress, osmosis-tolerant cultivar MM047 had higher H2S-producing capacity, which was impaired in osmosis-sensitive cultivar MM015. In MM015, alleviation of the osmotic stress-induced wilting phenotype and destruction of redox homeostasis were achieved by the application of NaHS (a H2S donor) at both low (10 μM) and high (200 μM) concentrations. Moreover, NaHS treatment mitigated osmotic stress-induced reduction on photosynthetic capacity in MM015, as evaluated by net photosynthetic rate and Rubisco carboxylation activity, etc. However, in MM047, a similar protective role against osmotic stress-triggered damage was observed only when NaHS was applied at low concentration, whereas aggravated at high dose. Importantly, we identified three genes encoding L-cysteine desulfhydrase (VrLCDs, EC 4.4.1.1) from mung bean genome, all of which possess H2S-producing enzymatic activities. The molecular function of VrLCD2, a major basal and inducible VrLCD form was subsequently investigated through A.rhizogenes-induced hairy roots system. Overexpression of this gene mitigated osmotic stress-triggered oxidative damage in osmosis-sensitive cultivar, which was exacerbated osmosis-sensitive cultivar. Taken together, our results demonstrated VrLCD-modulated endogenous H2S homeostasis regulates mung bean osmotic tolerance through maintaining redox homeostasis and photosynthetic capacity. These results further provide valuable resource for molecular breeding and genetic development of stress-resilient mung bean crop through the modulation of endogenous H2S homeostasis. •Mung bean osmotic stress tolerance was associated with the regulation of endogenous H2S homeostasis.•The maintenance of H2S homeostasis mitigated the osmotic stress-induced destruction of redox homeostasis and photosynthetic capacity in mung bean.•Osmotic stress tolerance was enhanced by overexpression of VrLCD2 in mung bean osmosis-sensitive cultivar, whereas exacerbated in osmosis-tolerant cultivar.